Application of the conflict of laws Spanish rule to determine the matrimonial property regime - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This judgement solves the Spanish law applicable to the matrimonial property regime of a couple in which she has Catalan civil status and he has common civil status. The appellant claims that the marital partnership system of Navarrese foral law applies and the husband claims that the regime is that of separation of property under Catalan law. To resolve the issue, the Provincial Court applies the connections of Article 9.2 CC and, given the situation that the couple do not have a common per- sonal law - according to the judgement - nor have they chosen a law in an authentic document before the marriage, it moves on to the third connection, according to which the applicable law is that of the common habitual residence immediately after the celebration of the marriage. At this point, the court finds that there is no common habitual residence immediately after the celebration of the nuptials, sin- ce the couple’s habitual residence in Pamplona began two months after this date. Therefore, the court concludes by applying the last connection of Article 9.2 CC, the law of the place of celebration of the marriage, to determine that the applicable regime is that of separation of property under Catalan law, as the nuptials were celebrated in Cabrils, Barcelona.